The effect of combined microwave and hydrogen peroxide pretreatment on sludge characteristics and oxidation status of waste activated sludge - Ambrose, H.; Philip, L.; Sen, Tushar; Suraishkumar, G. (Nova Science Publishers Inc, 2019)
No Abstract Available